LC3B, mTOR, AMPK Are Molecular Targets for Neoadjuvant Chemotherapy in Gastric Cancers - Liudmila V. Spirina; Alexandra V. Avgustinovich; Olga V. Bakina; Sergey G. Afanas’ev; Maxim Yu. Volkov; Amina Y. Kebekbayeva (Current Issues in Molecular Biology, 2022)
Autophagy plays a dual role in oncogenesis processes. On one hand, autophagy enhances the cell resistance to oncogenic factors, and on the other hand, it participates in the tumor progression. The aim of the study was to find the associations between the effectiveness of the FLOT regimen in resectable gastric cancers (GCs) with the key autophagy-related proteins. Materials and Methods: The study included 34 patients with morphologically verified gastric cancer. All patients had FLOT neoadjunvant chemotherapy (NACT) (fluorouracil, leucovorin, oxaliplatin, and docetaxel) followed by gastrectomy. The studied tissue material was the non-transformed and tumor tissues obtained during diagnostic video gastroscopy in patients before the start of the combined treatment and after surgical treatment, frozen after collection. The LC3B, mTOR, and AMPK expression was determined by real-time PCR. The content of the LC3B protein was determined by Western blotting analysis. Results: The mRNA level and the content of the LC3B protein were associated with the tumor stage and the presence of signet ring cells. The AMPK mRNA level was increased in patients with the T4N0-2M0 stage by 37.7 and 7.33 times, which was consequently compared with patients with the T2N0M0 and T3N0-1M0 stages. The opposite changes in the mTOR and AMPK in the GCs before anti-cancer therapy were noted. The tumor size and regional lymph node affections were associated with a decrease in the mTOR mRNA level. A decrease in the mTOR expression was accompanied by an increase in the AMPK expression in the GCs. The mTOR expression was reduced in patients with a cancer spreading; in contrast, AMPK grew with the tumor size. There was an increase in the LC3B expression, which can probably determine the response to therapy. An increase in LC3B mRNA before the start of treatment and the protein content in cancers after NACT with a decrease in therapy effectiveness was recorded. There was an increase in the protein level in patients with partial regression and stabilization by 3.65 and 5.78 times, respectively, when compared with patients with complete tumor regression was noted. Conclusions: The anticancer effectiveness in GCS is down to the LC3B, mTOR, and AMPK expression. These were found to be entire molecular targets affecting the cancer progression and metastasis as well as the NACT effectiveness.